What Beliefs Do Chilean Student Teachers, In-Service Teachers, and Teacher Educators Hold About Poverty? - Viviana de Lourdes Gomez-Nocetti (Revista Electrónica Educare)
The systematic failure of low socioeconomic levelchildren at school is a shared concern. What is the role of teachers and other involved individuals’ beliefs in maintaining this failure? This research answers the question: Are there differences in the beliefs between student teachers, in-service teachers, and Chilean teacher educators about the teaching and learning of literacy, and early math in the context of poverty? A questionnaire with two open questions and two Likert scales were applied to 265 student teachers, 66 in-service teachers and 25 teacher educators. With qualitative data, some descriptions were organized as “visions”; and with quantitative data, conglomerates and ANOVA were analyzed, based on Z scores. The results show: 1) negative view on school, children, and vulnerable families, 2) good teacher vision centered in affective-motivational features, 3) negative view on the family context shared to the whole sample, 4) over 70% had an intermediate vision on literacy beliefs and 50% on initial mathematics beliefs, 6) complex vision was the less present, 7) in-service teachers had the most stereotypical views regarding vulnerable schools, 8) only between 10% and 30% of teacher educators had complex beliefs. These results inform teacher education institutions about the beliefs and actors to whom their strategies for change should target.